Social Competencies of Productive Age Inclusion in The Work Industry in DKI Jakarta - Ratnasari, Dyah Nawang (UI Scholars Hub, 2023)
Background: Competencies of people with inclusion or disabilities of productive age in urban areas who have the opportunity to work in the work industry in the Special Capital Region (DKI) Jakarta. Aims: Seeing the relationship between the role of the world of work and their acceptance of inclusion or employment opportunities for inclusive children of productive age in Jakarta. Methods: This research was conducted using a qualitative approach using in-depth interview techniques with a single instrumental case study, employers and families of people with inclusion. Data was obtained from interviews with key and supporting informants, namely family and employers. In line with observation by sight, as well as in-depth and direct observation of the daily lives of people with disabilities. Results: The research results show that employees with disabilities in trusted companies have superior abilities consisting of intellectual, emotional and social abilities. Conclusion: The results of research and study findings on the social competence of people with disabilities who work formally and informally, it turns out that they have social competence and the potential to work well and seriously.